Merkel cell carcinoma - Bordeaux, Jeremy S.; Yu, Siegrid S.; Alam, Murad (Springer New York, 2013)
Merkel Cell Carcinoma is one of the first comprehensive, single-source clinical texts on the subject. Although not as common as melanoma, Merkel cell carcinoma is not rare - and it is both more deadly than melanoma and increasing at an epidemic rate. The book is clinical in focus and emphasizes treatment of this poorly understood cancer. Contributing authors include dermatologists, surgical oncologists, radiation oncologists, and medical oncologists from the US and around the world. Features: Comprehensive single-source clinical reference Treatment focus Written for practitioners, with emphasis on clinical relevance and quick retrieval of information Contributing authors represent all disciplines involved in treatment of Merkel cell carcinoma: dermatology, surgical oncology, radiation oncology, and medical oncology International in perspective, with contributors from US and abroad Members of active Merkel Cell Carcinoma Multicenter Interest Group have authored some of the chapters